Teaching and Learning Method in Inclusive Classroom: A Case Study in EAP Class at Sampoerna University - Anddy Steven; Athifah Utami; Rangga Akbar Sahidin; Victor Hutomo Desetyadi (Journal of Education and Learning (EduLearn), 2016)
A new challenge has appeared for Indonesian higher education to accommodate inclusive education. This study explored and compared the existing theories related with teaching and learning for inclusive education and teacher strategies applied in teaching hard of hearing students. From an observation in English for academic purposes classroom (EAP) course at Sampoerna University, this study evaluated the teaching and learning methods applied in the inclusive classroom and the students’ perspective upon the lesson. Through interviews conducted with the EAP lecturer, hard of hearing students, and a lecturer who is an expert in inclusive education, it can be seen that the usage of first language, written instructions, different types of instruction, and visualization through pictures, were able to facilitate the teaching and learning process for the hard of hearing students.